PENGELOLAAN SUMBER MATA AIR DI DESA KEDUNGOLENG KECAMATAN PAGUYANGAN KABUPATEN BREBES - Zulfa, Nely (WARTA, 2019)
Mountain springs as artesian springs and in a condition of continuity provided they are assisted by normal rainfall and an environment that remains green. In any season the mountain water source will continue to provide adequate water supply for the community. Kedungoleng Village is a village located in the hills in the District of Paguyangan, Brebes Regency. The hilly topography of the village of Kedungoleng and far from the springs is the weakness of the village to get clean water. Kedungoleng residents rely on rainwater, dug wells and public baths to fulfil their daily needs. Clean water in Kedungoleng Village comes from a spring in the hills, which is then accommodated in a public bath. This public bath is the only source of water that is easily available. It's just that all residents use so that sometimes residents fight over and are ineffective. The long-distance also requires considerable time and energy to bring clean water to the house. Some residents have dug wells, but the water is yellow and smelly and not suitable for drinking water consumption. The purpose of community service is to meet the needs of clean water for the community adequately and sustainably both in terms of quantity, quality and continuity to improve health and quality of life for the people in Kedung Oleng Village. This method of implementing community service activities designed water sanitation improvements in the form of making water tanks. Building water reservoirs are expected to be able to meet the needs of clean water at any time.